Heterogeneous fenton process using the mineral hematite for the discolouration of a reactive dye solution - Araujo,F. V. F. (2011)
This work reports a study on the heterogeneous Fenton reaction using hematite powder (Fe2O3) in suspension for the discolouration of the reactive dye Drimarene Red X-6BN in aqueous solutions. The efficiency of the process was studied as a function of the experimental conditions: initial pH; H2O2 dose; and hematite powder concentration; all of which showed a strong effect on the reaction kinetics. Under the best experimental conditions: pH = 2.5; H2O2 dose = 800 mg/L; and [Hematite] = 20 g/L, it was possible to remove about 99% of the initial colour in 120 minutes in a batch reaction at 25ºC. The analysis of the kinetic results suggests that the reaction is initiated by heterogeneous generation of free radicals on the hematite surface, but as soluble iron (III) and iron (II) species are released into the solution during the course of the reaction, a simultaneous homogeneous Fenton reaction step propagates and contributes to the overall reaction.